The Influence of Lifestyle on BMI Change for Tree-Month Injectable Hormonal Contraceptive Users - Zahroh, Asri Hikmatuz (Faculty of Public Health, 2015)
ABSTRACTTree-Month injectable hormonal contraceptive quarterly causes an increase in BMI. Increased BMI is one of the main reasons why the contraceptive users stopped their contraceptive. However, increased BMI was not experienced by all users, there are other factors that can influence increased BMI, such as consumption, physical activity and sedentary behaviour. The purpose of this study was to determine the effect of lifestyle to anthropometic change in the injectable hormonal contraceptive users. This study used observational analytic study and case control design. The sample size use simple random sampling technique. To determine the effect and odd ratio, this study used a simple logistic regression test. The results showed that lifestyle factor that affect and risk for anthropometric changein the three-month contraceptive users is sedentary behavior. Sedentary behavior â¥ 3 hours per day can increase the risk of increased BMI 9,048 times compared with sedentary behavior < 3 hours per day. The conclusion is sedentary lifestyle affected increased BMI among three- month injectable hormonal contraceptive users. By reducing sedentary behavior habit and increasing exercise behaviour, three-month injectable contraceptive users can prevent the risk of increased BMI.Keywords: contraceptive, acceptor, lifestyle, BMI, sedentary